Characteristics of Allopoietic Society and Proposal from the Perspective of PhD Candidates at FOŠ (Journal of Universal Excellence, 2026)
Research Question (RQ): We look into human kind and organization to establish why allopoietic internal and external environment is predominating.Purpose: In the article we present our view on the reality of modern society. We explain the definition of autopoiesis and allopoiesis principles of activity and reasons for allopoiesis situation.Method: We carried out an analysis of human potential between PhD Candidate of FOŠ (Faculty of Organizational Studies) by using quantitative methods.  We used the software tool R and we made a synthesis to capture the actual situation.Results: We found out that the majority of PhD Candidat dents perceive the society as non-free and immoral, without adequate strategies for improvement. Procedures and models were formulated, which we confirm as suitable for transformation of society according to the »top down« and »bottom up« principles to achieve integrity of individual, organizations and society. We organized motivational workshops with PhD Candidat and confirmed the compliance of methods for increasing moral potential and improving the activity of autopoietic networking.Organization: Self-organization is a method of autopoietic networking, which assures that allopoietic organization is surpassed.Society: By identifying the situation and reaching awareness of all institutions that an individual is a rich human potential and capital, which we need to invest in, the transformation to autopoietic society begins.Originality: We didn’t come across such credible research yet. Questionnaire and research passes condition of reality, that PhD Candidates of FOŠ would gain condition of internal and external environment is predominating.Restrictions / further research: The survey is limited to the population of FOŠ doctoral students. Such research is also useful in other faculties, institutions and the economic environment.
Keywords: allopoiesis; autopoiesis; human potential; human capital; self-organization; PhD Candidat FOŠ; moral society